The genera calliotropis seguenza and ambercyclus n. gen. (vetigastropoda, eucyclidae) from the early jurassic of Argentina - Ferrari, Silvia Mariel (2014)
The systematic position of the fossil species referred to Calliotropis is currently under debate due to the striking resemblance between these forms with their extant counterparts in general shell morphology and ornament pattern. We propose two temporal subgenera of Calliotropis: Calliotropis (Riselloidea) for Mesozoic species and Calliotropis (Calliotropis) for Cenozoic and Recent taxa. We also synonymize the families Eucyclidae and Calliotropidae, and redescribe the type genus of Eucylidae based on topotypic material of E. obeliscus from Normandy. We argue that the generic name Amberleya should be restricted to its type species Amberleya bathonica. For the species that were traditionally included in Amberleya, we propose the new genus Ambercyclus, with its type species Amberleya orbignyana. The present paper also provides descriptions of three Calliotropis species from the Early Jurassic marine deposits of Argentina. The occurrence of Calliotropis (Riselloidea) keideli n. sp., Calliotropis (Riselloidea) cf. C. (R.) keideli and Calliotropis (Riselloidea) sp. in the Jurassic of Chubut and Neuquén provinces represents a new record of the genus in Early Jurassic sediments of Argentina and South America. Moreover, two species of Ambercyclus n. gen., such as Ambercyclus espinosus and Ambercyclus? isabelensis n. sp., are described from the same deposits. Eucyclus, Amberleya, Ambercyclus, and Calliotropis are included into Eucyclidae, which we consider to be a family of Seguenzioidea.